Glucose Lowering Activity of Aqueous Ammodaucus leucotrichus Extract in Diabetic Rats - El-Ouady, Fadwa; Eddouks, Mohamed (Cardiovascular & Haematological Disorders - Drug Targets, 2020)
Background: Ammodaucus leucotrichus (Apiaceae) is a medicinal plant widely used by the Moroccan population to treat various diseases including diabetes. Aims: The aim of this study was to evaluate the antidiabetic effect of the aqueous extract prepared from the fruits of this medicinal plant. Normal and streptozotocin-induced diabetic rats were treated orally by the extract of Ammodaucus leucotrichus (A. leucotrichus) at a dose of 10 mg/kg. Methods: The blood glucose levels were determined during 6 hours and 15 days during this treatment. In addition the oral glucose tolerance test as well as the analysis of histopathological changes of liver was performed. The antioxidant activity of aqueous A. Leucotrichus extract was also valuated by the method of trapping of free radical 2,2-diphenyl-1 picrylhydrazyl (DPPH). Results: A. Leucotrichus fruit aqueous extract (ALFAE) reduced the blood glucose levels in both normal and diabetic rats. In addition, a remarkable influence on glucose tolerance was also noticed after ALFAE treatment. Moreover, ALFAE was able to exhibit a beneficial effect on histologlogical structure of liver. Finally a potential antioxidant effect has been shown in vitro. Conclusion: In conclusion, this study demonstrates the antihyperglycemic and hypoglycemic effects of A. Leucotrichus in rats supporting then its traditional use for the management of diabetes.
Keywords: lithiasis